Professional Subjectivity in the Swedish Healthcare Context: The Ambiguous Rehabilitation Coordinator - Flädjemark, Ulrika; Porter, Susann (Professions and professionalism, 2024)
The study examines a new professional function, the rehabilitation coordinator, in Sweden’s healthcare system. The rehabilitation coordinator acts as an inter-organizational facilitator in the return-to-work process. Using a Foucauldian perspective, the rehabilitation coordinator as a subject could be considered both as an objectified function shaped by governmental regulation and as a process by which the individual chooses how to perform the role. The rehabilitation coordinator must navigate between legislative regulations and adhere to their own professional ethics, resulting in varying forms of subjectivity. Metaphors used by rehabilitation coordinators provide insights into how individuals perceive their ethical responsibilities and how they approach interactions with patients and healthcare professionals. The paper underscores the ambiguity of the role and sheds light on how diverse considerations inherent in professional roles but also within the subject molds professional subjectivity in the Swedish healthcare system.